Evaluation of the failure modes and load-bearing capacity of different surface-treated polyether ether ketone copings veneered with lithium di-silicate compared to polyether ether ketone copings veneered with composite: An in vitro study - Abhishek Kumar Gupta; Rekha Gupta; Shubhra Gill (Wolters Kluwer Medknow Publications, 2021)
Aims: The purpose of this study is to compare and evaluate the failure modes and load-bearing capacity of different surface-treated polyether ether ketone (PEEK) copings when veneered with lithium di-silicate with that of PEEK veneered with composite. Settings and Design: In vitro; comparative study. Materials and Methods: Congruently anatomically shaped single unit PEEK copings (n = 40) were fabricated by scanning a prepared typodont tooth. The PEEK copings were subdivided among four groups (n = 10/group). Among all, one group of PEEK coping was veneered with Urethane dimethacrylate (UDMA)-based composite and other groups were veneered with lithium-di-silicate after different surface treatment on peek copings, i.e., (i) composite veneered PEEK fixed dental prosthesis (FDP) (control group: Group PC), (ii) lithium di-silicate veneered PEEK FDP (no surface treatment: Group PCeN), (iii) lithium di-silicate veneered PEEK FDP (sandblasting with 50 μm alumina: Group PCeS), and (iv) lithium di-silicate veneered PEEK FDP (chemical etching with 98% sulfuric acid: Group PCeE). The load-bearing capacity of all specimens was assessed using a universal test machine. All the samples were loaded till the cracking point and load at that point and failure modes were noted down. Statistical Analysis Used: One-way ANOVA and post hoc Tukey tests. Results: The highest load-bearing capacity was recorded for lithium di-silicate veneered PEEK copings which were chemically etched with 98% sulfuric acid (Group PCeE: 1040.25 ± 77.46) followed by Group PCeS (1017.20 ± 53.70), then Group PC (965 ± 51.57) and least was for Group PCeN (933 ± 97.54). There was a significant reduction in mean load-bearing capacity in Group PCeN (P < 0.05). Conclusions: Veneering of PEEK with pressed lithium di-silicate seems to be a viable clinical option in terms of adequate load-bearing capacity. Lithium di-silicate veneered PEEK FDPs were successful against physiological occlusal forces and are a suitable material for FDPs.